Why Do Bank Finance Clients Prefer Mark-up to Profit Loss Sharing Principles? Evidence from Islamic Rural Banks and Small to Medium Enterprises in Indonesia - Imronudin, Imronudin; Hussain, Javed Ghulam (International Journal of Economics and Financial Issues, 2016)
This study examines the preferences of Islamic rural banks clients in choosing Islamic financial contracts to finance their business. Mixed method, combining quantitative and qualitative approaches, was adopted in this study. Quantitative data was gathered from the Indonesian Financial Service Authority to examine the preferences of Small to Medium Enterprises (SMEs) in utilizing types of Islamic financial contracts. Qualitative data was collected by interviewing Islamic Rural Bank (BPRS) managers to investigate the reasons for choices of types of Islamic financing contracts. The finding shows that people prefer to use contracts under mark-up principles rather than Profit Loss Sharing (PLS) principles. Simplicity of the contracts was the main reason for choosing mark-up contracts. This trend affects the growth of mudaraba and musharaka contracts, and ultimately the growth of Islamic banks. Keywords: Islamic bank, SME’s preferences, profit and loss sharing. JEL Classification: G210